Upaya Meningkatkan Kemampuan Menghitung melalui Media Konkret Papan Penjumlahan dan Pengurangan (Panjurang) - Rahmawati, Rahmawati; Tahir, Muhammad; Khaerudin, Khaerudin (Mataram University, 2025)
This study aims to improve the arithmetic skills of first-grade students at SDN 23 Mataram through the use of concrete media called the Panjurang Board (Addition and Subtraction Board). The method used was Classroom Action Research (CAR), consisting of a pre-cycle and two cycles. The research subjects were 14 students. Data were collected through observation and learning outcome tests. The pre-cycle results showed that most students had difficulty performing calculations, with 28.57% categorized as